The Ethics of Advanced AI Assistants - Gabriel, Iason; Manzini, Arianna; Keeling, Geoff; Hendricks, Lisa Anne; Rieser, Verena; Iqbal, Hasan; Tomašev, Nenad; Ktena, Ira; Kenton, Zachary; Rodriguez, Mikel; El-Sayed, Seliem; Brown, Sasha; et al. (arXiv, 2024)
This paper focuses on the opportunities and the ethical and societal risks posed by advanced AI assistants. We define advanced AI assistants as artificial agents with natural language interfaces, whose function is to plan and execute sequences of actions on behalf of a user, across one or more domains, in line with the user's expectations. The paper starts by considering the technology itself, providing an overview of AI assistants, their technical foundations and potential range of applications. It then explores questions around AI value alignment, well-being, safety and malicious uses. Extending the circle of inquiry further, we next consider the relationship between advanced AI assistants and individual users in more detail, exploring topics such as manipulation and persuasion, anthropomorphism, appropriate relationships, trust and privacy. With this analysis in place, we consider the deployment of advanced assistants at a societal scale, focusing on cooperation, equity and access, misinformation, economic impact, the environment and how best to evaluate advanced AI assistants. Finally, we conclude by providing a range of recommendations for researchers, developers, policymakers and public stakeholders.
arXiv:2404.16244 [cs] <标题>: 高级 AI 助手的道德规范 <AI Smry>: The paper starts by considering the technology itself, providing an overview of AI assistants, their technical foundations and potential range of applications, then explores questions around AI value alignment, well-being, safety and malicious uses, and considers the deployment of advanced assistants at a societal scale.
Keywords: Computer Science - Computers and Society